The adventures of Ibn Battuta : a Muslim traveler of the 14th century - Dunn, Ross E. (University of California Press, 2012)
Ross Dunn here recounts the great traveler's remarkable career, interpreting it within the cultural and social context of Islamic society and giving the reader both a biography of an extraordinary personality and a study of the hemispheric dimensions of human interchange in medieval times.